Rising trend of Enterococcus species as pathogen, and its antimicrobial susceptibility pattern in western Gujarat - Chotaliya, Gaurav; Mehta, Krunal; Shingala, Hitesh; Kateshiya, Pushpa; Teraiya, Anshu V (The Journal of Infection in Developing Countries, 2025)
Introduction: Infections by enterococci pose a unique challenge as their ability to grow in extreme environments and intrinsic resistance to cephalosporin, clindamycin, and multidrug resistance. Enterococcus faecalis and Enterococcus faecium cause infections ranging from urinary tract infections (UTI) to bacteremia. Methodology: A retrospective study on urine and blood specimens was conducted over 11 months (February–December 2024) to assess the prevalence, age-gender distribution, species isolation, and vancomycin resistant enterococci (VRE) profile to aid treatment. A total of 4,549 urine and 4,070 blood samples were processed and identified by conventional bacteriological methods. The drug susceptibility was assessed based on the Clinical and Laboratory Standards Institute (CLSI) guidelines using the disc diffusion method. E. faecalis (94.05%) outnumbered E. faecium (5.94%). Results: Enterococci prevalence rose to 7.08% among positive samples compared to 4.1% in 2023 and 2.70% in 2022. Females had more prevalence (69.30%) than males (30.69%); and the 21–40 years age group was the most common. Both species were most resistant to ampicillin and ciprofloxacin. High level aminoglycosides (HLA) and vancomycin resistance were 54.55% and 15.15% in E. faecalis, and 66.67% and 33.33% in E. faecium, respectively. Nitrofurantoin (69.69% sensitive) and fosfomycin (78.79% sensitive) can be good options for E. faecalis while formulating broad spectrum therapy for UTI. VRE isolation was 7.92%. Conclusions: The rising trend of enterococci and the alarming rates of resistance highlight the need for rational and restricted drug use, with early detection and use of the susceptibility report to prevent treatment failures and spread of resistance.